ANALISIS HUBUNGAN FAKTOR INDIFIDU TERHADAP KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI PADA PEKERJA LAS. DI PT.PAL INDONESIA - Baiq Fathin Ayu Rakhmawati (JURNAL SANGKAREANG MATARAM, 2019)
PT. PAL is one of International-standard shipyards in Indonesia. PT.PAL uses sophisticated technology so it can compete internationally. Many works are needed to make one ship. Welding is one of the works that commonly done in the process of making ship but it has high risk of accident. One of the reasons that cause accident during welding process is the negligence in the use of proper personal protective equipment based on the operational standard of PT. PAL Indonesia. The research was a quantitative research with cross sectional approach. This research used observation method by observing the use of personal protective equipment during the welding process. The variables used in this research were the characteristics of the workers (age, working period, working status, education, and knowledge).The subjects of the research were 72 weld workers. Data were collected by observing directly using check list table cased on the standard operating system that used in PT. PAL Indonesia. The results showed that knowledge the determining factors with 0,02, it means that workers with little knowledge to violate the rule to use the personal protective equipment than the ones with knowledge.